Situation Report: Czechoslovakia, 19 February 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Trade Union Plenum The Leading Role of the Party in the Economy Personnel Changes in the Czechoslovak-Soviet Friendship League Novelist Ota Filip Sentenced